PENGARUH PEMBELAJARAN MODEL OBSERVASI LAPANGAN (OUTDOOR STUDY) DAN PEMBELAJARAN INQUIRY TERHADAP HASIL BELAJAR MATA PELAJARAN SOSIOLOGI SISWA IPS SMA NEGERI 3 PROBOLINGGO - Muhammad Dipo Islam Samsudin (Jurnal Penelitian dan Pendidikan IPS, 2016)
This research aims to know the influence of outdoor study model and inquiry learning on sociology learning achievement of social students at SMA Negeri 3 Probolinggo. Sixty three (63) social students were invoked as respondents. Further, it was found that there was significant influence of outdoor study model on sociology learning achievement, inquiry learning on sociology learning achievement, and outdoor study model and inquiry learning on sociology learning achievement.